Research on Carbon Emission Reduction Effect of China’s Carbon Trading Pilot: Based on Different in Different Method - Wang, Linshan; Liu, Chuanming; Yang, Xi (Advances in Social Sciences Research Journal, 2020)
Carbon emissions trading is one of the important ways to reduce carbon emissions by giving CO2 emission rights a commodity attribute that allows them to trade on the market and to reduce greenhouse gas emissions through the market mechanisms. Based on the inter-provincial panel data from 1997 to 2016, this paper constructs a basic theoretical analysis framework to analyze the carbon emission reduction effects of carbon trading policies, adopts PSM-DID to study the carbon emission reduction effects of carbon trading pilots. This study finds that: (1) The implementation of the carbon trading pilot can promote carbon emission reduction, but the pilot provinces and municipalities have different economic development levels, industrial structure and supporting measures adopted after the implementation of the carbon trading pilot policy, resulting in differences in carbon emission reduction effects between pilot provinces. (2) For the seller of carbon emission rights, carbon emission reduction is achieved through three effects of "market return-inducing", "technical innovation incentive" and "government support"; for the buyer, carbon emission reduction is achieved through three effects of "enterprise cost pressure", "process innovation motivation" and "market guiding". (4) The results of traditional PSM-DID further prove that the carbon trading pilot can significantly reduce CO2 emissions.